Digital Competencies of Social Studies Teachers amid Digital Transformation in Saudi Arabia - Al-Ameri, Fawzia Al-Hassan; Najmuddin, Hanan Abdel Jalil (Journal of Educational and Psychological Sciences, 2022)
This research aims to determine "The digital competencies of social studies teachers in light of digital transformation in the Kingdom of Saudi Arabia and to identify the degree of their possession of them from their point of view and to find out the difficulties they encounter when using digital competencies. The descriptive survey method was used for this purpose, and the research sample consisted of (711) female social studies teachers, who were randomly selected from schools in five towns in the Kingdom of Saudi Arabia, namely Riyadh, Jeddah, Madinah, Dammam and Abha. To achieve the research goal, the researcher built a three- topic questionnaire to collect data (the said topics are: personal data, the degree of the possession of digital competencies by social studies teachers from their point of view and the difficulties they encounter when using digital competencies). The study showed a number of results, which are:- The degree to which social studies female teachers possess digital competencies as a whole from their point of view is a great degree of possession of these competencies, with an average of 4.16.- And the assessment of social studies teachers of the difficulties they face when using the digital competencies required for digital transformation during teaching was generally large, with an average of 3.63.- The difficulty of "the great deal of professional burdens and commitments of female teachers" ranked first among the difficulties faced by female social studies teachers, with an average of 4.27.- While the two difficulties such as "the lack of awareness of teachers of the importance of employing digital competencies in the educational process"; and the “absence of qualified management for the successful application of digital competencies” ranked last and penultimate, with an average of 3.23; 3.39 respectively.The researcher suggested several recommendations, including keenness to develop the digital competencies among social studies teachers, inclusion of digital competencies development programs for social studies teachers before and during service to improve their teaching performance, and addressing the difficulties that impede the progress of social studies teachers towards the applications of digital competencies.
Keywords: digital transformation; digital competencies; social studies teachers